Suppression characteristics of multi-layer metal wire mesh on premixed methane-air flame propagation - Feng, Xiangrui; Zhang, Hongming; Si, Fangyuan; Dou, Jiawei; Li, Mingxuan; Wu, Long; Wang, Shengkang; Zhao, Lanming (Frontiers in Materials, 2023)
Metal wire mesh is widely used in the energy industry for its excellent protective properties as a fire stopping and explosion isolating material. In this study, the suppression characteristics of different layers of metal mesh on the dynamic behavior of premixed methane-air flame propagation were studied experimentally. A high-speed photographic schlieren system was used to photograph the explosion process to capture the changes in the microstructure of the flame, and high-frequency pressure sensors and micro-thermocouple measurements were used to capture the flame explosion pressure and temperature. The experimental results show that the suppression effectiveness of wire mesh is a reflection of the coupling of explosive flame propagation behavior and combustion state in the pipe. Increasing the number of mesh layers and mesh density can destroy the microstructure of the premixed methane-air flame front and hinder the progress of flame propagation. Increasing the number of wire mesh layers will delay the peak time of premixed flame propagation speed and reduce the peak speed values of flame propagation. Wire mesh has a pronounced attenuation effect on premixed flame temperature and explosion overpressure. The maximum flame temperature attenuation rate is 34.99%–60.95%, and the maximum explosion overpressure attenuation rate is 33.70%–74.02%. And the suppression effect is greatly enhanced as the increase of mesh layers.